Polymorphisms of the phosphodiesterase 4D, cAMP-specific (PDE4D) gene and risk of ischemic stroke: a prospective, nested case-control evaluation - Zee, Robert Y L; Brophy, Victoria H; Cheng, Suzanne; Hegener, Hillary H; Erlich, Henry A; Ridker, Paul M (Stroke (1970), 2006)
In an Icelandic population, gene variants of the phosphodiesterase 4D, cAMP-specific (PDE4D) gene were reported to be risk predictors for ischemic stroke. Case-control studies in other populations have yielded mixed evidence for association. A recent analysis in a prospective, non-Icelandic study found an association with stroke after stratification by hypertension. We evaluated nine PDE4D single nucleotide polymorphisms (SNPs) among 259 incident ischemic stroke cases and 259 controls were matched on age and smoking status and length of follow up since randomization, all drawn from initially healthy white males within the Physicians' Health Study cohort who were prospectively followed for first-ever stroke events. Genotype and allele distributions were similar between cases and controls. Results from single-marker conditional logistic regression analysis adjusting for traditional stroke risk factors showed significant association of SNP56 with risk of ischemic stroke (recessive odds ratio [OR], 2.26; 95% confidence interval [CI], 1.11 to 4.61; P=0.03). Among the participants without baseline hypertension, SNP42 (additive OR, 1.68; 95% CI, 0.99 to 2.86, P=0.06), SNP45 (dominant odds ratio, 2.24; 95% CI, 1.00 to 5.00, P=0.05), and SNP56 (additive odds ratio, 1.77; 95% CI, 1.02 to 3.10, P=0.04) showed modest association with increased risk of ischemic stroke. We found modest associations between several PDE4D gene polymorphisms and risk of incident ischemic stroke in men without baseline hypertension in this prospective, non-Icelandic study. Although of borderline statistical significance, the direction and magnitude of the effect for SNP42 parallels that observed in a recent study evaluating women from an independent, nested case-control study.